Histone Methylation: Achilles Heel and Powerful Mediator of Periodontal Homeostasis. (November 2020) - Francis, M.; Gopinathan, G.; Foyle, D.; Fallah, P.; Gonzalez, M.; Luan, X.; Diekwisch, T.G.H.
The packaging of DNA around nucleosomes exerts dynamic control over eukaryotic gene expression either by granting access to the transcriptional machinery in an open chromatin state or by silencing transcription via chromatin compaction. Histone methylation modification affects chromatin through the addition of methyl groups to lysine or arginine residues of histones H3 and H4 by means of histone methyl transferases or histone demethylases. Changes in histone methylation state modulate periodontal gene expression and have profound effects on periodontal development, health, and therapy. At the onset of periodontal development, progenitor cell populations such as dental follicle cells are characterized by an open H3K4me3 chromatin mark on RUNX2, MSX2, and DLX5 gene promoters. During further development, periodontal progenitor differentiation undergoes a global switch from the H3K4me3 active methyl mark to the H3K27me3 repressive mark. When compared with dental pulp cells, periodontal neural crest lineage differentiation is characterized by repressive H3K9me3 and H3K27me3 marks on typical dentinogenesis-related genes. Inflammatory conditions as they occur during periodontal disease result in unique histone methylation signatures in affected cell populations, including repressive H3K9me3 and H3K27me3 histone marks on extracellular matrix gene promoters and active H3K4me3 marks on interleukin, defensin, and chemokine gene promoters, facilitating a rapid inflammatory response to microbial pathogens. The inflammation-induced repression of chromatin on extracellular matrix gene promoters presents a therapeutic opportunity for the application of histone methylation inhibitors capable of inhibiting suppressive trimethylation marks. Furthermore, inhibition of chromatin coregulators through interference with key inflammatory mediators such as NF-kB by means of methyltransferase inhibitors provides another avenue to halt the exacerbation of the inflammatory response in periodontal tissues. In conclusion, histone methylation dynamics play an intricate role in the fine-tuning of chromatin states during periodontal development and harbor yet-to-be-realized potential for the treatment of periodontal disease.